An iron-doped NASICON type sodium ion battery cathode for enhanced sodium storage performance and its full cell applications. Issue 39 (29th September 2020) - Park, Jae Yeol; Shim, Yoonsu; Kim, Yong-il; Choi, Yuseon; Lee, Ho Jun; Park, Jungjae; Wang, Ji Eun; Lee, Yonghee; Chang, Joon Ha; Yim, Kanghoon; Ahn, Chi Won; Lee, Chan-Woo; et al.
Abstract : Substantial Fe substitution into a vanadium-based NASICON cathode is demonstrated to boost a cathode performance and materialize a superior sodium ion battery. Abstract : The development of high performance and cost-effective electrode materials is the main challenge for the commercialization of sodium ion batteries. Here, we suggest a substantial iron-doped sodium vanadium fluorophosphate and sodium vanadium phosphate composite as a promising cathode. Iron substitution enhances ionic diffusivity and lowers the bandgap, and, thus, improves sodium storage performance. The origin of the enhanced performance is investigated employing in situ X-ray diffraction, ex situ X-ray photoelectron spectroscopy, density functional theory calculation, and electrochemical characterization. Moreover, we demonstrate its full cell configuration with earth-abundant element-based copper sulfide anodes. The suggested cathode and sodium ion battery full cell exhibits well-balanced sodium storage performance in terms of energy density, C-rate capability, cycling stability, and low cost. The low cost and high performance of the full cell make it an attractive choice for energy storage systems and high power applications to support lithium ion batteries.